Perspectives on the Management of Surplus Dairy Calves in the United States and Canada - Creutzinger, Katherine; Pempek, Jessica; Habing, Gregory; Proudfoot, Kathryn; Locke, Samantha; Wilson, Devon; Renaud, David (Frontiers in Veterinary Science, 2021)
The care of surplus dairy calves is a significant issue for the United States and Canadian dairy industries. Surplus dairy calves commonly experience poor welfare as evidenced by high levels of mortality and morbidity, and negative affective states resulting from limited opportunities to express natural behaviors. Many of these challenges are a result of a disaggregated production system, beginning with calf management at the dairy farm of origin and ending at a calf-raising facility, with some calves experiencing long-distance transportation and commingling at auction markets or assembly yards in the interim. Thus, the objectives of this narrative review are to highlight specific challenges associated with raising surplus dairy calves in the U.S. and Canada, how these challenges originate and could be addressed, and discuss future directions that may start with refinements of the current system, but ultimately require a system change. The first critical area to address is the management of surplus dairy calves on the dairy farm of origin. Good neonatal calf care reduces the risk of disease and mortality, however, many dairy farms in Canada and the U.S. do not provide sufficient colostrum or nutrition to surplus calves. Transportation and marketing are also major issues. Calves can be transported more than 24 consecutive hours, and most calves are sold through auction markets or assembly yards which increases disease exposure. Management of calves at calf-raisers is another area of concern. Calves are generally housed individually and fed at low planes of nutrition, resulting in poor affective states and high rates of morbidity and mortality. Strategies to manage high-risk calves identified at arrival could be implemented to reduce disease burden, however, increasing the plane of nutrition and improving housing systems will likely have a more significant impact on health and welfare. However, we argue the current system is not sustainable in long-term and new solutions for surplus calves must be considered. A coordinated and holistic approach including substantial change on source dairy farms and multiple areas within the system used to market and raise surplus dairy calves, can lead to more sustainable veal and beef production with improved calf outcomes.